Solve the following expression:
− 3 × − 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Your rule isn't quite correct. It's
[...] only when a ≥ 0 or b ≥ 0
or another way
[...] only when at least one of a , b is non-negative.
Log in to reply
I have edited my solution. I thought people will understand it but it is not correct. Thanks for informing.
− 3 × − 2 = − 1 × 3 × − 1 × 2 = ( − 1 ) 2 × 2 × 3 = − 1 × 6 = − 6
Problem Loading...
Note Loading...
Set Loading...
− 3 × − 2 = 3 − 1 × 2 − 1 = 3 i × 2 i = 6 i 2 ( Here i 2 = − 1 )
− 3 × − 2 = − 6